Exploration and Investigation of Periodic Elements for Electrocatalytic Nitrogen Reduction. Issue 45 (18th September 2020) - Patil, Shivaraj B.; Wang, Di‐Yan
Abstract: High demand for green ecosystems has urged the human community to reconsider and revamp the traditional way of synthesis of several compounds. Ammonia (NH3 ) is one such compound whose applications have been extended from fertilizers to explosives and is still being synthesized using the high energy inhaling Haber‐Bosch process. Carbon free electrocatalytic nitrogen reduction reaction (NRR) is considered as a potential replacement for the Haber‐Bosch method. However, it has few limitations such as low N2 adsorption, selectivity (competitive HER reactions), low yield rate etc. Since it is at the early stage, tremendous efforts have been devoted in understanding the reaction mechanism and screening of the electrocatalysts and electrolytes. In this review, the electrocatalysts are classified based on the periodic table with heat maps of Faraday efficiency and yield rate of NH3 in NRR and their electrocatalytic properties toward NRR are discussed. Also, the activity of each element is discussed and short tables and concise graphs are provided to enable the researchers to understand recent progress on each element. At the end, a perspective is provided on countering the current challenges in NRR. This review may act as handbook for basic NRR understandings, recent progress in NRR, and the design and development of advanced electrocatalysts and systems. Abstract : This review focuses on electrocatalytic properties of periodic elements toward the nitrogen reduction reaction. Recent advancements and working mechanisms of various elements are illustrated with appropriate tables and graphs. Overall, this review intends to open different directions for the fabrication of high efficiency electrocatalysts.